A Study on the Effect of Perceived Functional Risk on the Public’s Purchase Intention in Green Sports Stadium Services—Based on the Perspective of Motivational Protection Theory - Chenfan Liu; Kai Guo; Jinhao Wu; Kai Zhao; Hao Li; Longrui Qi (Buildings, 2025)
Environmental pollution has become a significant issue, and environmental protection within the realm of sports has garnered increasing attention from various sectors of the academic community. This study takes the public’s intention to purchase sports stadiums as the research object, introduces two mediating variables of green value perception and sense of accomplishment, builds a hypothetical model from the perspective of motivation protection theory, and explores the influence of perceived functional risk of green sports stadiums on consumption intention through SEM analysis based on the samples of the recovered questionnaires (N = 1073). The results are as follows: first, there is a negative influence between perceived functional risk and green sports stadium consumption intention, and the lower the perceived functional risk of green sports stadiums, the more consumers can promote their choice of green sports stadiums when they consume in stadiums; second, green value perception plays a mediating role in the relationship between perceived functional risk and green sports stadium services consumption intention; third, a sense of accomplishment plays a mediating role in the relationship between perceived functional risk and willingness to consume green sports stadium; fourth, green value perception and a sense of accomplishment play a chain mediating role between perceived functional risk and willingness to consume in the context of green sports stadiums. This study aims to contribute to the popularization and development of green sports stadiums in China and to provide green sports stadium builders and managers with more targeted and effective marketing strategies.